RESULTS AND PROSPECTS OF SANITARY AND EPIDEMIOLOGICAL WELL-BEING ENSURING FOR THE POPULATION OF RUSSIAN FEDERATION - G. G. Onischenko (Радиационная гигиена)
The report states priority goals of sanitary and epidemiological service and shows the analysis of the Service's administrative reforms and structural changes from 1991 to 2007. It considers the existing regulatory and legal background on all aspects of hygiene and epidemiology as well as the Concept of the Federal Service Development. It analyses the work of Rospotrebnadzor  bodies in ensuring of sanitary and epidemiological well-being of the population, including current state of population radiation protection in Russian Federation.